GENERALIZATION OF THEORETICAL AND METHODOLOGICAL PRINCIPLES OF GOALS AND MECHANISMS OF INVESTMENT POLICY AT THE REGIONAL LEVEL - BOIKO, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines issues of formation and implementation of state investment policy at the regional level. Based on these principles, the purpose of the study is to substantiate the conceptual characteristics of the investment policy for the development of the regional economic complex. The essence of the concept of regional investment policy has been specified. Strategic tasks, target orientations and priorities of the regional investment policy have been determined. The leading forms and methods of regional investment policy are indicated. The system of mechanisms and instruments of regional investment policy is summarized. Using the method of theoretical generalization, it was established that investment policy is one of the leading components of state economic policy, which involves the formation and application of a system of methods, forms, mechanisms and measures of state influence on the investment environment, intensity, volumes and structural characteristics of investments, conditions and the flow of investment processes with the aim of a systemic integrated approach to the reconstruction of the economy at the stage of post-war reconstruction. The combination of forms and methods of investment policy largely determines its strategic orientation, including the construction of a system of mechanisms, tools and means, which, in turn, are not constant, but vary depending on the state of economic development, business climate, financial and resource opportunities on all levels of management. Taking into account regional specifics, the combination of mechanisms used within the investment policy is formed according to the following vectors: (1) complex, (2) functional, (3) partial.